Interactive teaching kit / Jamal Hussaini … [et al.] - Hussaini, Jamal; Mohd Nor, Fadzilah; Adnan, Ariza; Palanisamy, Navindra Kumari; Jumahat, Noor Masyitah (Division of Research and Industry Linkages, 2017)
As a lecturer and researcher in medical microbiology, I have observed if we do not stimulate inquisitiveness and interest in students, there will be a lack of desire to learn. Due to lack of facility and improper infrastructure, teaching of medical microbiology can be challenging. Hence we have created a teaching kit that can provide a complete experience (visual, hands on and interactive) of learning medical microbiology without having access to any specific requirements or facilities. This kit is made with the intention of making the learning of microbiology simple and easy. The kit comes with organism pictures on culture plate and their microscopic slide in actual petri dish and microscope slide respectively. This will provide a safe learning environment without having to handle the actual pathogenic organism. Users also get the opportunity to have a hands on experience on how bacteria is grown. This kit handbook is coded with interactive features which can be unlocked with any type of smart phone or tablet. Download the free app for ios and Android and experience the live demo and videos.